Вимірювання параметрів і обробка інформації в інтелектуальній системі електроживлення (Smart Grid) - Поворознюк, Назар Іванович; Бобрівник, Катерина Євгенівна (My University, 2012)
Розглянуті тенденції розвитку енергетичних систем. Проаналізований сучасний етап розвитку систем енергозабезпечення і вказані проблеми і виклики. Обґрунтована необхідність підвищення якості вимірювання параметрів енергосистем. Запропонований алгоритм синхронізованих вимірювань векторів напруги і струму на основі вейвлет-перетворення і проаналізовані похибки вимірювань. A monitoring quality power systemquality is considered. The contemporary stage of development of energy systems and indicated the problems and challenges are analysed. The necessity of monitoring power system is grounded. The structure of the system for monitoring power quality and signal analysis algorithms based on wavelet transform and classification distortion based on support vector method are proposed Trends in power systems is considered. The contemporary stage of development of power systems and indicated the problems and challenges are analysed.. The necessity of improving the quality of measurement of energy. The proposed algorithm is synchronized measurements of voltage and current phasors based on wavelet transform and analyze measurement errors.
Keywords: інтелектуальна система вимірювання; вейвлет-перетворення; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки